Combined Effect of Acid Salts with Clove and Cinnamon Oils on Controlling of Postharvest Decay in Carrot - Nanasombat, Suree; Phunpruch, Saranya (My University, 2025)
Fungal decay in carrots is a serious problem during postharvest storage. The present work aimed to study the antifungal effect of ammonium carbonate (AC) or potassium metabisulfite (PM) in combination with cinnamon or clove oils on delaying carrot decay caused by black rot mold during chill storage. In vitro trials were conducted to determine the antifungal activity of those acid salts, essential oils and their combinations against selected fungi isolated from carrots. Alternaria sp. C7D7 isolated from carrots was inhibited by AC and PM at 0.5-1.0% w/v minimum inhibitory concentration (MIC), while cinnamon and clove oils possessed strong anti-Alternaria effect with 0.025% w/v MIC. The combination of AC or PM at 0.25-0.5% w/v with cinnamon or clove oils at 0.04-0.25% w/v in potato dextrose agar produced a 100% antifungal index. Synergy testing by the checkerboard method showed that the combination of AC and cinnamon oil had partial synergistic effects against the mold. The optimum concentrations of combined AC or PM and cinnamon or clove oil were selected to formulate dipping solutions for carrot treatments. Their effect on controlling black rot decay in carrots during chill storage was investigated. The treatment with the dipping solutions consisting of combined 0.5% AC with 0.25% cinnamon oil or 1% AC alone caused a lower percentage of black rot decay (13.9-19.4% decay) in carrots compared to the others during storage at 5°C for 10 weeks. These findings show the usefulness of cinnamon oil and AC or their combination on delaying black rot decay in carrots.
Keywords: Alternaria; ammonium carbonate; antifungal effect; antifungal effect; potassium metabisulfite